Effects of Potassium/Lidocaine‐induced Cardiac Standstill During Cardiopulmonary Resuscitation in a Pig Model of Prolonged Ventricular Fibrillation. (April 2014) - Kook Lee, Byung; Joon Lee, Seung; Woon Jeung, Kyung; Youn Lee, Hyoung; Jeong, In Seok; Lim, Victor; Hun Jung, Yong; Heo, Tag; Il Min, Yong; Olson, James E.
Abstract Objectives Several studies in patients who underwent open heart surgery found that myocardial ischemic damage was reduced by potassium cardioplegia combined with lidocaine infusion. The authors evaluated the effects of potassium/lidocaine‐induced cardiac standstill during conventional cardiopulmonary resuscitation (CPR) on myocardial injury and left ventricular dysfunction after resuscitation from prolonged ventricular fibrillation (VF) cardiac arrest in a pig model. Methods Ventricular fibrillation was induced in 16 pigs, and circulatory arrest was maintained for 14 minutes. Animals were then resuscitated by standard CPR. Animals were randomized at the start of CPR to receive 20 mL of saline (control group) or 0.9 mEq/kg potassium chloride and 1.2 mg/kg lidocaine diluted to 20 mL (K‐lido group). Results Seven animals in each group achieved return of spontaneous circulation (ROSC; p = 1.000). Four of the K‐lido group animals (50%) achieved ROSC without countershock. Resuscitated animals in the K‐lido group required fewer countershocks (p = 0.004), smaller doses of epinephrine (p = 0.009), and shorter durations of CPR (p = 0.004) than did the control group. The uncorrected troponin‐I at 4 hours after ROSC was lower in the K‐lido group compared with the control group (2.82 ng/mL, 95% confidence interval [CI] = 1.07 to 3.38 ng/mL vs. 6.55 ng/mL, 95% CI = 4.84 to 13.30 ng/mL; p = 0.025), although the difference was not significant after Bonferroni correction. The magnitude of reduction in left ventricular ejection fraction (LVEF) between baseline and 1 hour after ROSC was significantly lower in the K‐lido group (26.5%, SD ± 6.1% vs. 39.1%, SD ± 6.8%; p = 0.004). Conclusions In a pig model of untreated VF cardiac arrest for 14 minutes, resuscitation with potassium/lidocaine‐induced cardiac standstill during conventional CPR tended to reduce myocardial injury and decreased the severity of postresuscitation myocardial dysfunction significantly.